The Effect of Explicit Instruction on the Acquisition of Words’ Visual Aspects By Second-Grade French-Speaking Children - Ruberto, Noémia; Daigle, Daniel; Ammar, Ahlem; Beaulieu, Judith (Language and Literacy / Langue et littératie, 2024)
This paper explores the most efficient teaching context to learn words’ visual aspects and by second-grade French-speaking children, including those with special needs. Students came from six classrooms and each classroom was randomly assigned to the control group or to one of two experimental interventions (TFS: explicit teaching of semantic and formal properties of words; TF: explicit teaching of formal properties of words). For students without difficulties, the experimental interventions have contributed equally to the learning of the words’ visual aspect, whereas no progress was observed for the control group. For students with special needs, only the intervention that combined explicit instruction of semantic and formal properties lead to significant progress. These results suggest that explicit instruction should focus on the semantic and formal properties of words, especially for students with special needs.